Влияние меди на цитоскелет разных типов клеток корней Arabidopsis thaliana - Горюнова, И.И.; Емец, А.И. (Фактори експериментальної еволюції організмів, 2015)
Aims. Copper (Cu) is a micronutrient that has roles in photosynthesis, respiration, antioxidant activity, cell wall metabolism and hormone perception. Excess Cu is toxic and therefore its delivery has to be tightly regulated. Methods. Light and fluorescent microscopy, laser scanning confocal microscope. Results. It was shown for the first time that copper (5– 20 µM) induced Arabidopsis thaliana (GFP-FABD2) primary root growth inhibition accompanied with morphological alterations, reorientation and/or depolymerization of actin filaments in cells of meristematic, transition and elongation root zones. Conclusions. The results showed that the study of cell response to copper toxicity can happen marker for excess copper in the environment.